2003
DOI: 10.1002/cne.10698
|View full text |Cite
|
Sign up to set email alerts
|

Octopaminergic modulation of synaptic transmission between an identified sensory afferent and flight motoneuron in the locust

Abstract: The role of the biogenic amine octopamine in modulating cholinergic synaptic transmission between the locust forewing stretch receptor neuron (fSR) and the first basalar motoneuron (BA1) was investigated. The amines 5-hydroxytryptamine (5-HT, serotonin) and dopamine were also studied. Bath application of octopamine, 5-HT, and dopamine at concentrations of 10(-4) M reversibly decreased the amplitude of monosynaptic excitatory postsynaptic potentials (EPSPs) evoked in BA1 by electrically stimulating the fSR axon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 83 publications
4
14
1
Order By: Relevance
“…Since the CS on the leg are also activated during walking, and can aid in the transition between the stance and swing phases of movement (Newland and Emptage, 1996), and also activate the SETi that receives many parallel sensory inputs to FETi (Newland and Kondoh, 1997), it likely that dopamine modulates the outputs of other components of the neural networks controlling limb movement and hence leads to the reduced locomotion found in solitarious locusts (Roessingh et al, 1993; Simpson et al, 1999). The effects of dopamine on the flight system described previously by Leitch et al (2003) also show that this transmitter has effects consistent with it decreasing synaptic activity in specific flight motor neuron of gregarious locusts. While a functional significance for the role of dopamine on the flight system was not discussed at that time it now appears that its effects are consistent with a more general role for dopamine in orchestrating phase change and phenotypic plasticity.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Since the CS on the leg are also activated during walking, and can aid in the transition between the stance and swing phases of movement (Newland and Emptage, 1996), and also activate the SETi that receives many parallel sensory inputs to FETi (Newland and Kondoh, 1997), it likely that dopamine modulates the outputs of other components of the neural networks controlling limb movement and hence leads to the reduced locomotion found in solitarious locusts (Roessingh et al, 1993; Simpson et al, 1999). The effects of dopamine on the flight system described previously by Leitch et al (2003) also show that this transmitter has effects consistent with it decreasing synaptic activity in specific flight motor neuron of gregarious locusts. While a functional significance for the role of dopamine on the flight system was not discussed at that time it now appears that its effects are consistent with a more general role for dopamine in orchestrating phase change and phenotypic plasticity.…”
Section: Discussionsupporting
confidence: 70%
“…We also found that serotonin levels were increased on isolation of gregarious locusts. Leitch et al (2003) showed that such an increase in serotonin levels could reduce a sensory-evoked cholinergic input onto flight motor neurons and thereby reducing their excitability, which could underpin the reduced flight activity in solitarious desert locusts.…”
Section: Discussionmentioning
confidence: 99%
“…OA and TA are decarboxylation products of the amino acid tyrosine, with TA as the biological precursor of OA. In insect flight systems, OA assumes a variety of physiological roles affecting central neuron excitability (Ramirez and Pearson, 1991), synaptic transmission (Evans and O'Shea, 1979;Leitch et al, 2003), sensory sensitivity (Matheson, 1997), hormone release (Orchard et al, 1993), and muscle metabolism (Mentel et al, 2003). Almost every organ is equipped with OA receptors (Roeder, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recordings from rhythmically active preparations have also shown that the stretch receptor can modulate ongoing rhythmic activity in flight motor neurons (Pearson et al, 1983). The direct excitatory connection between the stretch receptor and the depressor motor neurons, which probably involves the release of several hundred vesicles during each excitatory post-synaptic potential, is modulated by octopamine and may also be modulated by pre-synaptic GABAergic inputs (Judge and Leitch, 1999;Simmons, 2001;Leitch et al, 2003). Yet these studies have not altered the role proposed by Burrows for the stretch receptor (Burrows, 1975).…”
mentioning
confidence: 99%